Project girl - McDonald, Janet 1954-2007 (Univ. of Calif. Press, 2000)
The powerful account of a young woman's struggle to realize her dreams while remaining true to who she was before attending Ivy League schools and receiving impressive diplomas. It tells of the spectacular failures and unlikely comebacks of a ghetto kid whose academic talent opens doors onto a world of private schools, rich classmates, and plum jobs but who back home confronts a neighborhood of growing poverty, drug abuse, and crime.
Keywords: McDonald, Janet <1953->; Weibliche Schwarze. Amerika; African American women -- New York (State) -- New York -- Biography; Gifted girls -- New York (State) -- New York -- Biography; Inner cities -- New York (State) -- New York; Public housing -- New York (State) -- New York; Brooklyn (New York, N.Y.) -- Biography; Brooklyn (New York, N.Y.) -- Social conditions; New York (N.Y.) -- Biography; New York (N.Y.) -- Social conditions; Biografie